An enzyme-free alcohol-based organoid harvesting solution - Jimmy Maillard; Lisa Pickard; Udai Banerji (BioTechniques)
Three-dimensional (3D) cell culture is a more physiologically relevant model for drug development than two-dimensional (2D) cell culture. A common method to culture cells in 3D consists in embedding cells in synthetic or animal-based matrices that provide structural support for cell growth. They partially mimic in vivo conditions and enable scalable culture. Here, we introduce an alcohol-based Solution for Harvesting Organoids Efficiently, denoted SHOE. We tested its harvesting potential on 2 cell lines grown as spheroids and 2 patient-derived organoids. It enables rapid, high-yield cell recovery, at room temperature (RT), and bypasses prolonged cold incubation of standard protocols. It preserves 3D structure and growth in subsequent passages.